Decoding Codes on Graphs: Low Density Parity Check Codes - Nori, Aditya (Resonance: Journal of Science Education, Indian Academy of Sciences, 2003)
The fundamental problem of communication is that of reproducing at one point either exactly or approximately a message selected at another point. [ Claude Shannon, 1948.